Qualification of a Distribution Contract in Judicial Practice of Kazakhstan, Germany and Latvia - DILMUKHAMETOV, Salavat L.; SARINA, Salima A.; DUISENOVA, Elmira O.; NESTEROVA, Elena V.; TURUNTAEVA, Albina A. (Journal of Advanced Research in Law and Economics; Vol 7 No 7 (2016): JARLE Volume 7, Issue 7(21), Winter 2016, 2017)
The lack of legislative regulation of distribution relations, on the one hand and active use of structures of a distribution agreement – on the other hand, often lead to contradictory interpretation of the legislation and to judicial errors. Therefore, the study of issues, related to qualification and registration of distribution contracts, is undoubtedly relevant both from theoretical and practical point of view. Based on materials of law enforcement and judicial practice, the author investigates the matter on qualification of a distribution contract by courts in such countries as Kazakhstan, Germany and Latvia. Taking into account specificity of the distribution contract, its place in the system of civil law contracts of these countries is determined.